Using Geochemical Evidence to Determine Provenance in a High Arctic Glacier-Fed Lake, Linné Valley, Svalbard, Norway - Thomas, Elizabeth (2009)
Elizabeth studied the geochemistry of the various sediment source areas in the Linne' Valley. She also attempted to reconstruct the relative contribution of these different source areas by looking at down-core data